2011
DOI: 10.1186/1559-0275-8-7
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant glycosylation associated with enzymes as cancer biomarkers

Abstract: BackgroundOne of the new roles for enzymes in personalized medicine builds on a rational approach to cancer biomarker discovery using enzyme-associated aberrant glycosylation. A hallmark of cancer, aberrant glycosylation is associated with differential expressions of enzymes such as glycosyltransferase and glycosidases. The aberrant expressions of the enzymes in turn cause cancer cells to produce glycoproteins with specific cancer-associated aberrations in glycan structures.ContentIn this review we provide exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
151
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(151 citation statements)
references
References 87 publications
0
151
0
Order By: Relevance
“…The external region of a cell membrane, known as the glycocalyx, is dominated by glycosylated molecules, which have important roles in these interactions (2). Therefore, the aberrant expression of various genes involved in glycan synthesis or degradation, which causes compositional changes of the glycocalyx, is frequently associated with malignant transformation (3)(4)(5). Recently, Zhao et al (6) reported the expression of human natural killer-1 sulfotransferase (HNK-1ST) to be strongly up-regulated in several subsets of murine and human melanoma cells during retinoic acid (RA) 2 mediated differentiation.…”
mentioning
confidence: 99%
“…The external region of a cell membrane, known as the glycocalyx, is dominated by glycosylated molecules, which have important roles in these interactions (2). Therefore, the aberrant expression of various genes involved in glycan synthesis or degradation, which causes compositional changes of the glycocalyx, is frequently associated with malignant transformation (3)(4)(5). Recently, Zhao et al (6) reported the expression of human natural killer-1 sulfotransferase (HNK-1ST) to be strongly up-regulated in several subsets of murine and human melanoma cells during retinoic acid (RA) 2 mediated differentiation.…”
mentioning
confidence: 99%
“…However, the clinical useful markers based on genomics and proteomics remain limited. In recent years, aberrant glycosylation has been recognized as a cellular hallmark event during carcinogenesis (Reis et al, 2010;Adamczyk et al, 2011), and it has been a topic for well characterization of tumor and better understanding the mechanism (Meany et al, 2011). Both N-and O-linked glycoproteins have been shown to be altered in a wide range of cancers, including CRC.…”
Section: Introductionmentioning
confidence: 99%
“…A wealth of proteomic and metabolomic technologies has been developed to gain insight into some of these downstream mechanisms. Post-translational regu latory mechanisms of interest, including proteinprotein interactions, glycosylation, phosphorylation, and ubiquitination, are being studied extensively to shed light on aberrations associated with diseased states [121][122][123][124] .…”
Section: Current Challenges and Future Directionsmentioning
confidence: 99%